2016
DOI: 10.1186/s40798-016-0059-7
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoxia Extends Time to Exhaustion During High-Intensity Intermittent Exercise: a Randomized, Crossover Study in Male Cyclists

Abstract: BackgroundSome endurance athletes exhibit exercise-induced arterial hypoxemia during high-intensity exercise. Inhalation of hyperoxic gas during exercise has been shown to counteract this exercise-associated reduction in hemoglobin oxygen saturation (SaO2), but the effects of hyperoxic gas inhalation on performance and SaO2 during high-intensity intermittent exercise remain unclear. This study investigated the effects of hyperoxic gas inhalation on performance and SaO2 during high-intensity intermittent cyclin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
0
9
0
1
Order By: Relevance
“…9 and 10). This has been demonstrated during both incremental tests and time to exhaustion (7,8,95,172,176,186,205,207,213,217,221,228,229,258,290,315). Although it has been observed that the magnitude of increase in exercise capacity correlates with the increase in Ca O 2 in the hypoxemic range [e.g., exercise-induced arterial hypoxemia (190)], our analysis of the available literature as seen in Figs.…”
Section: Acute Effects On Performancementioning
confidence: 87%
“…9 and 10). This has been demonstrated during both incremental tests and time to exhaustion (7,8,95,172,176,186,205,207,213,217,221,228,229,258,290,315). Although it has been observed that the magnitude of increase in exercise capacity correlates with the increase in Ca O 2 in the hypoxemic range [e.g., exercise-induced arterial hypoxemia (190)], our analysis of the available literature as seen in Figs.…”
Section: Acute Effects On Performancementioning
confidence: 87%
“…In line with previous findings, 57% of our participants showed EIAH at intensities near to maximum; 7 of the 11 cyclists in the NORM, and 6 of the 12 cyclists in HYPER. The lower the SaO 2 during exercise intensity near to maximum the larger is the effect of acutely breathing hyperoxia on exercise tolerance (Ohya et al, 2016). Therefore, it can be expected that maintaining Hb fully saturated at an exercise intensity near to VO 2 max in cyclists who otherwise exhibit EIAH in normoxia would lead to improved skeletal muscle training adaptations resulting from the increased O 2 delivery.…”
Section: Discussionmentioning
confidence: 99%
“…reduced peak twitch force postexercise) to that of hypoxic and normoxic exercise in which a lower power output is maintained. Others have also demonstrated that hyperoxia decreases muscle and blood lactate concentrations during submaximal and maximal exercise (Byrnes, Mihevic, Freedson, & Horvath, 1984;Ohya, Yamanaka, Ohnuma, Hagiwara, & Suzuki, 2016;Plet et al, 1992;Stellingwerff et al, 2005). This might reflect increased oxidation rates of pyruvate and reduced net glycogen utilization (i.e.…”
Section: Effect Of Hyperoxia On Performancementioning
confidence: 98%